A Decade of Civil Service Reform in Sub-Saharan Africa - Lienert, Ian (IMF Working Papers; Working Paper, 1997)
This paper assesses a decade of experience in civil service reform in a sample of 32 sub-Saharan African countries. Many countries have made an important start towards reducing excessive staffing levels and the nominal wage bill, but less progress has been made in decompressing salary differentials in favor of higher-grade staff. In the CFA franc zone countries, real wages fell sharply after the 1994 devaluation, but the wage bill relative to tax revenue is still high in many countries. There is a need to consolidate quantitative first-generation reforms that contribute to macroeconomic stabilization. Equally important is the need to make progress on qualitative second-generation reforms, especially remuneration and promotion policies that reward performance and measures to improve civil service management. Such policies will require strong political commitment by governments.